Network performance evaluation of selected voice codec using OPNET / Farra Nydia Amran - Amran, Farra Nydia (2010)
Voice Over Internet Protocol (VoIP) is a relatively new technology and it has already achieved wide acceptance and use. It has so far proved to be a good candidate for replacing the POTS (Plain Old Telephone System). It, of course, has drawbacks along with the numerous advantages it brings and one of it is coding and compression which is the codec. Codec are not only used for compression, but also for encoding, which, is the translation of analog voice into digital data that can be transmitted over IP networks. The quality and efficiency of the compression software therefore has a big impact on the voice quality of VoIP conversations. Using three widely use codec; performance evaluation of these codec had been made to make better understanding of the major characteristics of the codec to improve the quality of voice services. Different performance aspects were investigated in this project including, average end to end delay, throughput and jitter. By using OPNET simulation software, the three codec were compared and analyzed. This project simulation results indicated that each codec performance were different according to performance metrics that had been selected.